Constructing an entrepreneurship project evaluation system using a hybrid model - Shao, Qi-Gan; Liou, James J. H.; Weng, Sung-Shun; Su, Peiyao (Journal of Business Economics and Management, 2020)
Due to the economic trends around the world and the strong support and guidance of relevant governments, the number of entrepreneurial projects has soared in China. It is necessary to construct a standard assessment system for entrepreneurial projects that is comprehensive and effective. This study extracted six dimensions and 23 criteria for evaluating entrepreneurial projects. This study applies the best and worst methods to obtain the weights of the dimensions and criteria. Then, the Technique for Order Preference by Similarity to an Ideal Solution method was used to evaluate the entrepreneurial projects in an entrepreneurial competition. The results show that team quality, the business model and entrepreneurship ability are the three most important dimensions for evaluating entrepreneurial projects. The improvement of the innovating ability, the training of the team and the value proposition are the three keys to successful implementation of the entrepreneurial projects.